2010
DOI: 10.1039/c0cp00467g
|View full text |Cite
|
Sign up to set email alerts
|

Model catalysts of supported Au nanoparticles and mass-selected clusters

Abstract: In surface science, much effort has gone into obtaining a deeper understanding of the size-selectivity of nanocatalysts. In this article, electronic and chemical properties of various model catalysts consisting of Au are reported. Au supported by oxide surfaces becomes inert towards chemisorption and oxidation as the particle size became smaller than a critical size (2-3 nm). The inertness of these small Au nanoparticles is due to the electron-deficient nature of smaller Au nanoparticles, which is a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 55 publications
(80 reference statements)
1
34
0
Order By: Relevance
“…Because of the reduced size of clusters, and the fact that a considerable fraction of their atoms are located at the cluster/support interface, these effects are likely to be more pronounced in cluster catalysts than typical nanoparticle catalysts, leading to modification of their structural and electronic character. Furthermore, a wide range of techniques including X-ray photoelectron spectroscopy (XPS) 21,22 , scanning tunnelling microscopy (STM) [23][24][25] , (scanning) transmission electron microscopy ((S)TEM) 26 , atomic force microscopy (AFM) 27 , and synchrotron methods [28][29][30] are available to characterize deposited clusters, and can be used to gain knowledge of their unique properties and interaction with support materials. Moreover, elaborate reactionsFischer-Tropsch, partial oxidation, polymerization 31 and dehydrogenation 32 processes, for example -that have complex reactants and products, and would be difficult to investigate in the gas phase, can be studied with deposited clusters.…”
mentioning
confidence: 99%
“…Because of the reduced size of clusters, and the fact that a considerable fraction of their atoms are located at the cluster/support interface, these effects are likely to be more pronounced in cluster catalysts than typical nanoparticle catalysts, leading to modification of their structural and electronic character. Furthermore, a wide range of techniques including X-ray photoelectron spectroscopy (XPS) 21,22 , scanning tunnelling microscopy (STM) [23][24][25] , (scanning) transmission electron microscopy ((S)TEM) 26 , atomic force microscopy (AFM) 27 , and synchrotron methods [28][29][30] are available to characterize deposited clusters, and can be used to gain knowledge of their unique properties and interaction with support materials. Moreover, elaborate reactionsFischer-Tropsch, partial oxidation, polymerization 31 and dehydrogenation 32 processes, for example -that have complex reactants and products, and would be difficult to investigate in the gas phase, can be studied with deposited clusters.…”
mentioning
confidence: 99%
“…The first route relies on classical surface science ultrahigh-vacuum (UHV) techniques. In this case, metal nanoparticles are created on flat supports, either via gas-phase delivery and supportassisted self-assembly [57] of metal atoms by evaporation of the metal [58][59][60] or by the deposition of size-selected clusters formed in the gas phase using various methodologies [61][62][63][64].…”
Section: Size Effects -Setting the Scenementioning
confidence: 99%
“…Ganteför and co-workers developed another instrument combining cluster deposition with STM and used this for a number of studies of Au n deposited on several supports [85][86][87][88]. This work has proceeded in collaboration with Kim and co-workers in Korea, recently focusing on gold chemistry under ambient conditions [32,[89][90][91]. Watanabe and co-workers have an instrument that allows STM, XPS, and high pressure reactivity studies of size-selected model catalysts [92] and have reported studies of CO oxidation over Pt n /TiO 2 (110) [11,93] and correlations with core level binding energies.…”
Section: Introductionmentioning
confidence: 96%
“…Understanding the effects of particle size is complicated by the fact that there is typically a broad distribution of sizes present, and it is generally not possible to vary size independently, without also changing other properties such as metal loading or support structure. Consider gold nanocatalysts, which have received tremendous attention over the past decade, using a wide variety of approaches [17,[29][30][31][32][33]. Much of the original work focused on the properties of Au nanoparticles in the 2-5 nm size range, because these were the obvious species detectable in conventional electron microscopy [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%